(untitled) (Research, Society and Development, 2026)
This study aimed to analyze the prevalence of arterial hypertension among older adults living in Pará de Minas and to identify associated factors. A quantitative, descriptive, and exploratory approach was adopted, using secondary data from the Diagnostic, Situational, and Epidemiological Survey of Older Adults in Pará de Minas (FAPAM, 2024). The methodology employed descriptive statistical analysis, including estimates of absolute and relative frequencies and the presentation of results through tables and graphs, in order to characterize the sociodemographic profile and explore associations with risk factors and comorbidities. The results indicated a high prevalence of arterial hypertension among older adults, associated with physical inactivity, excess weight, and low treatment adherence, as well as the coexistence of cardiometabolic comorbidities. It is concluded that strengthening nursing actions in Primary Health Care, with emphasis on health education, monitoring, and support for treatment adherence, is essential for hypertension control and the promotion of healthy aging in the municipality.